2008
DOI: 10.1016/j.jbiomech.2007.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the human brain induced by mild angular head acceleration

Abstract: Deformation of the human brain was measured in tagged magnetic resonance images (MRI) obtained dynamically during angular acceleration of the head. This study was undertaken to provide quantitative experimental data to illuminate the mechanics of traumatic brain injury (TBI). Mild angular acceleration was imparted to the skull of a human volunteer inside an MR scanner, using a custom MR-compatible device to constrain motion. A grid of MR "tag" lines was applied to the MR images via spatial modulation of magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 23 publications
12
146
1
Order By: Relevance
“…49,50 The most prominent example of high frequency mechanical modeling of brain tissue occurs in traumatic brain injury simulations, where viscoelastic models have been more commonly applied. [51][52][53][54] Initial experience in brain MRE also follows this trend-higher actuation frequencies use VE, whereas low frequency IA employs PE models. and 3 show the first examples of both PE and VE inversions of in vivo 50 Hz EA and 1 Hz IA MRE data, and VE is clearly preferable at higher frequencies, whereas PE works better at lower frequencies.…”
Section: B1 Discussionmentioning
confidence: 96%
“…49,50 The most prominent example of high frequency mechanical modeling of brain tissue occurs in traumatic brain injury simulations, where viscoelastic models have been more commonly applied. [51][52][53][54] Initial experience in brain MRE also follows this trend-higher actuation frequencies use VE, whereas low frequency IA employs PE models. and 3 show the first examples of both PE and VE inversions of in vivo 50 Hz EA and 1 Hz IA MRE data, and VE is clearly preferable at higher frequencies, whereas PE works better at lower frequencies.…”
Section: B1 Discussionmentioning
confidence: 96%
“…[13][14][15][16][17][18] Because of the ease with which the CC can be delineated by MR imaging as a region of interest along with being the largest commissural fiber tract in the brain, the CC is also the most widely investigated WM brain structure in TBI. 10,19 In a previous DTI studies of the CC in acute mTBI in adolescent patients, Wilde et al 17 found distinct DTI differences in the injured group. More important, findings were related to PCS indicating that DTI metrics not only have the potential to reveal neuropathologic changes associated with trauma but can clinically relate to the acute status of the patient who has a brain injury.…”
Section: ϫ3mentioning
confidence: 97%
“…[1][2][3][4][5][6][7] Detailed biomechanical and heuristics studies consistently show the vulnerability of WM, particularly the CC and longcoursing fasciculi, especially within frontotemporal regions. [8][9][10][11][12] DTI abnormalities within the CC in patients with TBI have been well documented in both the acute and chronic phase of injury. [13][14][15][16][17][18] Because of the ease with which the CC can be delineated by MR imaging as a region of interest along with being the largest commissural fiber tract in the brain, the CC is also the most widely investigated WM brain structure in TBI.…”
Section: ϫ3mentioning
confidence: 99%
“…Using a well-developed MR technology to place magnetic "lines" within an anatomic plane, it is striking to see how much the brain can move under a simple, repeated rotation in the horizontal plane [117,118]. Estimates of the intracranial strains that appear during physiological head rotations in volunteers show the shear strains can reach 0.05 mm/mm, which is near the thresholds for axonal damage but at much lower deformation rates.…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%